2005
DOI: 10.1007/s00125-005-1823-2
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of intermittently administered sodium fusidate in patients with newly diagnosed type 1 diabetes mellitus: the FUSIDM trial

Abstract: Aims/hypothesis: We evaluated in a double-blind study the effect of early treatment with the immunomodulatory drug fusidin in patients with newly diagnosed type 1 diabetes mellitus. Methods: Twenty-eight adults with newly diagnosed type 1 diabetes were included in the study. The patients were randomly assigned (computergenerated random number sequence) to two experimental groups. Patients allocated to the fusidin (FUS) group (n=15) received sodium fusidate (fusidin; 500 mg orally three times daily for 4 weeks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…To our knowledge, this is the first study in a large cohort of a Mediterranean National Registry for new cases of type 1 diabetes in which the accelerator hypothesis is tested. Our results did not fit with the hypothesis and point to the heterogeneity of the disease in different populations (14,15). Accordingly, in a recent study including children who were either from the U.K. or originally from the south of Asia, Porter et al did not confirm the accelerator hypothesis (9).…”
Section: Results -From 1990 To 2004contrasting
confidence: 83%
“…To our knowledge, this is the first study in a large cohort of a Mediterranean National Registry for new cases of type 1 diabetes in which the accelerator hypothesis is tested. Our results did not fit with the hypothesis and point to the heterogeneity of the disease in different populations (14,15). Accordingly, in a recent study including children who were either from the U.K. or originally from the south of Asia, Porter et al did not confirm the accelerator hypothesis (9).…”
Section: Results -From 1990 To 2004contrasting
confidence: 83%
“…The majority of these studies (n 5 80) were open label (78%). There were 13 blinded (single or double) studies [7][8][9][10][11][12][13][14][15][16][17][18][19] and 21 randomized trials, 12 of which were controlled, 5 with placebos [10,16,17,20,21]. One study, by Goncalves and Thorn [22], accounted for the majority (n 5 14,672) of exposures.…”
Section: Fusidic Acid Safety Data Pooled From the Published Literaturementioning
confidence: 99%
“…In an animal experiment, Fusidin could ameliorate the course of diabetes (Nicoletti F et al 2000). Although there are some other studies showed different result about the antibiotic improving diabetes (Conget I et al 2005), it is worth to do more in-depth study to uncover the function of that to regulate diabetes. 3-Hydroxyphenylacetic acid is an intermediate metabolite of quercetin metabolized by intestinal microbiome (Zabela V et al 2020), and lots of studies proved that quercetin has a function to treat T2D (Dhanya R. 2022).…”
Section: Discussionmentioning
confidence: 96%